POLITICAL PARTICIPATION UNDER CONDITIONS OF LOCAL GOVERNMENT REFORM IN UKRAINE - Кавилін, О. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article studies political participation and describes the processes of local government reform and decentralization that began after the Revolution of Dignity and that need improving of the level of public involvement. Local government is the way people can exercise their power as a form of democracy (in accordance with Article 5 of the Basic Law of Ukraine) and it is also one of the modern democratic system foundations that provides the possibility of independent functioning without any interferences on the part of public authorities on the basis of self-organization and self-financing. Local government is a key part of the civil society that cannot be conceived without competent and responsible participation of citizens in making and implementing of managerial decisions.